2018
DOI: 10.1038/s41598-018-28055-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of Magnoliae Flos extract in mouse hippocampal neuronal cells

Abstract: Magnoliae Flos (MF) is a traditional medicinal herb used for managing rhinitis, sinusitis and headache. The purpose of the present study was to determine the neuroprotective effect of MF against glutamate-induced oxidative stress and to assess the underlying mechanism. Glutamate is a major endogenous excitatory neurotransmitter in the brain and contributes to the development of neurodegenerative diseases by excessive activation. MF extract was subjected to a neuroprotective effect assay in HT22 mouse hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Plant extracts containing these compounds have antioxidant properties and are known to effectively suppress neuronal apoptosis caused by glutamate [ 25 , 26 ]. In this study, we used mouse-derived HT22 nerve cells to study the neuroprotective effect of catechins against glutamate-induced cell apoptosis and to decipher the neuroprotective mechanism of action [ 27 ]. These cells are widely used to study neuroprotection against glutamate damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant extracts containing these compounds have antioxidant properties and are known to effectively suppress neuronal apoptosis caused by glutamate [ 25 , 26 ]. In this study, we used mouse-derived HT22 nerve cells to study the neuroprotective effect of catechins against glutamate-induced cell apoptosis and to decipher the neuroprotective mechanism of action [ 27 ]. These cells are widely used to study neuroprotection against glutamate damage.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been reported that neuronal apoptosis induced by glutamate is mainly caused by oxidative stress, which is a result of excessive production of free radicals and low levels of antioxidants in cells [ 27 ]. In addition, previous studies have reported that phytochemical antioxidants inhibit neuronal cell death by preventing the accumulation of free radicals [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…FM has been successfully applied to treat and relieve several conditions, such as allergic rhinitis, headache, sinusitis, and rheumatoid arthritis. Several FM pharmacological effects, including antiallergic, anti-bacterial, anti-inflammatory, anti-rheumatic, and anti-angiogenic activities, have been previously reported [23,[32][33][34][35][36]. Although many reports have indicated the effects of whole FM extracts on intracellular calcium signaling via SOCE, those of its isolated constituents are still under speculation [22].…”
Section: Discussionmentioning
confidence: 99%
“…It contains various bioactive compounds, such as lignans (magosalin, magnosalicin, magnone A, B, magnolin, eudesmin), essential oils (a-pinene, cineole, citral, eugenol, and capric acid), and alkaloids [(−)-coclaurine, (−)-N-methylcoclaurine, (+)-reticuline] ( Yun and Kim, 2021 ). A previous study showed that a Magnoliae Flos methanol extract protected against glutamate-mediated oxidative stress in mouse hippocampal neuronal cells ( Jung et al, 2018 ). Recently, Chen et al (2020) suggested that Magnoliae Flos essential oil can act as an immunosuppressant because it suppressed cytokine (TNF-α) production in LPS-stimulated dendritic cells.…”
Section: Introductionmentioning
confidence: 99%